Science Experience as correlate of student learning outcome - Oluwasina Bukola Timothy (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
Biology as the science of life is designed ultimately to educate individuals so that they can acquire knowledge about the basic essentials of living things and those of their community. Therefore, In this paper, we want to examine whether the students experiences in Biology Class will accomplish understanding and success in the learning outcome. Our sample is 500 Secondary School II students in Akinyele Local Government of Oyo state, in Biology Class. We used a survey design of the correlational type. Instruments used are Students Attitude to Biology Questionnaire (r=0.83), Science Experiences Inventory in Biology (r=0.72), and Students Achievement Test in Biology (r=0.76). The study reveals that the relative effect of Science experiences on attitude (?=0.228, t = 5.128; p<0.05) was significant, a negative, non-significant relationship between science experience (r = -0.024; p>0.05) and students’ achievement in Biology. Therefore, the findings of the study show that Science experience was the independent variable that strongly predicts students' attitude to Biology. Students should therefore be exposed to science experiences that will enhance a better attitude to Biology.